Safety and efficacy of tocilizumab for rheumatoid arthritis: a systematic review and metaanalysis of clinical trial studies - Amal Saki; Elham Rajaei; Fakher Rahim (Rheumatology, 2021)
The present systematic review and meta-analysis was conducted to assess the effect of tocilizumab (TCZ) in patients with rheumatoid arthritis (RA). We systematically searched all potential articles in the main databases, including PubMed, Scopus, EMBASE, Web of Sciences (ISI), and Cochrane Center. The search was subsequently updated in December 2020. The initial review and extraction of information were performed independently by two authors to collect the first author and publication year; sample size; mean age of the intervention and control groups; the dose of TCZ, and the follow-up duration. Outcomes of interest include the ACR20, ACR50, ACR70, total complication rate, and the occurrence of remission. Any disagreements between the reviewers were resolved by discussion and re-check of the article and consultation with a third reviewer. After reviewing and culling, 15 clinical trials comparing the clinical efficacy of TCZ and its comparators in the treatment of patients with RA entered the qualitative and quantitative synthesis. Tocilizumab 8 mg was statistically better than 4 mg or placebo for ACR responses. Significant clinical adverse events in patients with RA treated with TCZ, such as abnormal liver function tests (LFTs) and infections, were more frequent than in comparator groups. This systematic review and meta-analysis suggest that the combination therapy of TCZ with other drugs such as methotrexate and disease-modifying antirheumatic drugs has been studied for various clinical effects concerning safety and clinically significant adverse events. Although the data are promising, long-term performance and safety data need to be fully identified, as well as the risks and benefits of TCZ, especially appropriate timing, dosage, and regimen.